Potential field method: obstacle avoidance for mobile robots - Duong, Ngoc Lan; Ngo, Van Thuyen (Journal of Technical Education Science, 2010)
Potential field method is a universal method in obstacle avoidance applications for mobile robots. This method is particularly attractive because of its elegance and efficiency for obstacle avoidance. Other methods such as Bug algorithm, dynamic window approach are also presented in this paper. Simulation results on Player/Stage (run on Linux) show that the potential field methods are very efficient for local obstacle avoidance and navigation.